PEMBINAAN MORALITAS NARAPIDANA MELALUI PENDIDIKAN PRAMUKA DI LEMBAGA PEMASYARAKATAN KELAS IIB PATI - Novianto, Erwin; Rachman, Maman (Civic Education Program, Universitas Negeri Semarang, 2015)
Class IIB Penitentiary Pati has played an important role in providing moral guidance to prisoners through scouts education. This study is to examine the implementation and the barriers of the moral education through education scouts in Class IIB Pati Penitentiary. This study uses qualitative research methods. The results of the research shows that the development of morality through education has been running well partly because it uses among system, in which the supervisor set an example / role model to members of the scout. scoutmaster also get advanced course basis (KMD) as a guide to teach members of the scout class IIB Pati penitentiary. The inhibiting factor in the development of morality through education in a correctional institution Scout class IIB Pati, includes the diverse background of scouts training among the trainers, the lack of facilities in the clothing, and the lack of cooperation of the outside parties. Efforts to overcome barriers to the development of morality through the use of among system.